PELATIHAN BAHASA INGGRIS KOMUNIKATIF BAGI KELOMPOK SADAR WISATA DI DESA CARANG SARI BADUNG UTARA - I N. Sudipa; F. I M. Brata; I M. Rajeg; L. P. Laksminy; N. K. Sri Rahayuni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2010)
This Community Service was conducted in Carangsari-Badung Utara, July-August 2010 in the form of Communicative English Training for the members of Tourism Awareness Group (Pokdarwis). The members mostly work in providing services in terms of rafting, tracking, elephant camp, horse riding and safari as the potential tourism attractions owned by this village. The training materials were given through the respective steps namely : Orientation, Drills, Feedback and Continuation. It turns out that the members of Pokdarwis managed to improve their communicative ability since they have experienced in using English previously. The members expected the team to continue giving more training in the future.